Role of Natural Immunomodulator (Aloe Vera) in Cellular and Humoral Immune Responses - Wiedosari, Ening (Indonesian Animal Sciences Society, 2007)
Aloe vera belongs to a group of Liliaceae family plant and cultivated worldwide. It possesses acemannan (acetylated mannan), which has a significant pharmacological property. The acemannan has an immunomodulatory activity when administered to animals. The major immunomodulating effect includes the activation of immune effector cells, such as lymphocytes and macrophages, resulting in the production of cytokines, interleukin (IL)-1, IL-6, IL-12 and tumor necrosis factor alpha (TNFÎ±). In particular, this extract can modulate the differentiation capacity of CD4+T cells to mature into Th1 subsets and enhance the innate cytokine response. As a consequence, this extract will have a profound effect in controlling disease, caused by intracellular infectious agents (bacteria and viruses). However, further studies are needed to determine the immunomodulating effects of Aloe vera in multi-component extracts equivalent to what are beingÂ used commonly in traditional medicine. Â Key words: Aloe vera, immunomodulator, cytokines